2017
DOI: 10.1142/s021830131750001x
|View full text |Cite
|
Sign up to set email alerts
|

Strangeness production in high-energy collisions and Hawking–Unruh radiation

Abstract: The assumption that the production of quark-antiquark pairs and their sequential string-breaking taking place through the event horizon of the color confinement determines freezeout temperature and gives a plausible interpretation of the thermal pattern of pp and AA collisions. When relating the black-hole electric charges to the baryon-chemical potentials it was found that the phenomenologicallydeduced parameters from various particle ratios in the statistical thermal models agree well with the ones determine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
11
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 61 publications
11
11
2
Order By: Relevance
“…Also, we find that the generic (non)extensive temperature decreases with the increase in both particle masses and strange qunatum numbers, while the Boltzmann temperature shows an opposite dependence. On the other hand, it is worthy highlighting that the generic (non)extensive temperature obtained agrees well with previous studies [44,45], in which it was concluded that the freezeout of such particles with large masses and large strange quantum numbers takes place earlier than the one for light particles with small strange quantum numbers. [1].…”
Section: B Correlations Between Resulting Fit Parameterssupporting
confidence: 91%
See 2 more Smart Citations
“…Also, we find that the generic (non)extensive temperature decreases with the increase in both particle masses and strange qunatum numbers, while the Boltzmann temperature shows an opposite dependence. On the other hand, it is worthy highlighting that the generic (non)extensive temperature obtained agrees well with previous studies [44,45], in which it was concluded that the freezeout of such particles with large masses and large strange quantum numbers takes place earlier than the one for light particles with small strange quantum numbers. [1].…”
Section: B Correlations Between Resulting Fit Parameterssupporting
confidence: 91%
“…First, T G obtained from the generic (non)extensive statistics agrees well with refs. [44,45] but apparently disagrees with ref. [54].…”
Section: A Statistical Fits To Pt Spectracontrasting
confidence: 66%
See 1 more Smart Citation
“…The value of both temperatures (Tsallis and Boltzmann) increase with the increasing in both the particle mass and the strangeness number and also with the multiplicity classes for all systems. The direct relationship between the temperature and the strangeness number of hadrons is unlike the known behaviour obtained previously in extensive models (particle yields and ratios) [53,54], so we will work on the confirmation of the behaviour of this dependence in extensive and nonextensive particle yields and ratios in future work. Our calculations are compared with the modified Tsallis results [30] and agreed with each other.…”
Section: Resultsmentioning
confidence: 76%
“…this quantity is averaged in such a statistical ensemble. It was shown that the freezeout temperature likely vary with the number of strange quarks included in[42,43].…”
mentioning
confidence: 99%